Enhancing Elementary Literacy Through the 'Class Lit-eracy Tree': A Strategic Case Study of the 'One Week One Book' Program - Nurisah Sumartina; Hidayat, Hidayat (CV. Media Digital Publikasi Indonesia, 2026)
Creating a literate generation requires a sustained pedagogical process, a goal often challenged by resource limitations in formal education. This study addresses this gap by examining an innovative, low-cost strategy. Introduction: This research describes a literacy learning strategy using a 'Class Literacy Tree' (POLIKEL) to support the 'One Week One Book' (SAMI SAKU) program and its impact on the reading interest and literacy skills of fifth-grade elementary students. Method: A qualitative, descriptive case study design was employed at two elementary schools in Sumedang Regency, Indonesia. Data were collected via observation, in-depth interviews, and documentation analysis, then analyzed using an interactive model. Results: The 'Class Literacy Tree' strategy successfully creates a joyful, participatory, and goal-oriented learning environment. The program effectively fosters continuous reading and writing habits, with teachers acting as crucial facilitators. Students' consistent, tangible engagement with the 'tree' demonstrated marked improvement in reading interest, comprehension of intrinsic text elements, and basic writing skills. Discussion: The strategy's success is contingent on a supporting management cycle strong school leadership, validating the PDCA cycle as a framework for sustainable pedagogical innovation. This strategy serves as an effective, sustainable, and scalable alternative model to enhance foundational literacy in elementary education.